Avoiding the "brick wall of awkward": Perspectives of youth with autism spectrum disorder on social-focused intervention practices. (February 2016) - Bottema-Beutel, Kristen; Mullins, Teagan S; Harvey, Michelle N; Gustafson, Jenny R; Carter, Erik W
Many youth with autism spectrum disorder participate in school-based, peer-mediated intervention programs designed to improve their social experiences. However, there is little research discerning how these youth view intervention practices currently represented in the literature, information which could improve the social validity of intervention programming. In this mixed-methods study, we interviewed 33 youth with autism spectrum disorder about seven social-focused, peer-mediated intervention components. We asked participants to rate the favorability of each component to determine their degree of liking. Subsequently, we asked participants to give a rationale for their rating, in order to explore influencing factors. Chi-square tests indicated that high ratings were most prevalent for recruiting peers and family involvement and medium ratings were most prevalent for meeting with peers . Analyses of variance also indicated that preferences in the specific format intervention components were delivered. Several themes emerged from our qualitative analysis of open-ended responses, including the ramifications of adults in adolescent social life, the advantages of learning through shared activities with peers, and the effects of disclosing disability status. Our findings will offer guidance for researchers and practitioners interested in individualizing interventions to reflect student preferences. Furthermore, we document areas of concern for youth with autism spectrum disorder as they access school-based interventions.